2017
DOI: 10.24057/2071-9388-2017-10-4-43-68
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox for Sediment Budget Research in Small Catchments

Abstract: ABStrACt. Sediment monitoring and assessment remain one of the most challenging tasks in fluvial geomorphology and water quality studies. As a response to various environmental and human disturbance effects, the main sources and pathways of the sediments transported within catchments, especially most pristine small one, may change. The paper discusses state-of-the-art in the sediment budget research for small catchments. We identified nine independent approaches in the sediment transport assessment and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…This is very important in areas, where no or only limited sediment-related studies have been done in the past. We found that almost no studies have been devoted to ecohydrology, hydromorphology and sediment transport in transboundary catchments of Eastern Europe (Chalov et al, 2017b;Krengel et al, 2018). The proposed approach might be a useful tool to fill these knowledge gaps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is very important in areas, where no or only limited sediment-related studies have been done in the past. We found that almost no studies have been devoted to ecohydrology, hydromorphology and sediment transport in transboundary catchments of Eastern Europe (Chalov et al, 2017b;Krengel et al, 2018). The proposed approach might be a useful tool to fill these knowledge gaps.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the Western Dvina does not flow through either country, parts of Lithuania and Estonia drain into the WDRB. The gauging network is sparse and data has a lot of gaps, especially related to water and sediment qual-ity (Chalov et al, 2017b). It is characterized by six stations representing a drainage area of 17 000 km 2 with water discharges monitoring and one single sediment monitoring station at the outlet of the catchment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average slope of the upper reach is 10.2 per cent and the stream valley development V (calculated according to [41]) is 0.364. The orographic index (λ) of 777.48 according to [42] classifies the Mlynne stream as a high-mountain watercourse and the Łochtin stability parameter (f) of 0.913 [43] defines the Mlynne stream riverbed as being vulnerable to erosion.…”
Section: The Mlynne Streammentioning
confidence: 99%
“…Hysteresis classes are used to identify physical processes in the watersheds. For example, clockwise hysteresis indicates that the source of sediment could be the outlet of the watershed, while counterclockwise loop hysteresis indicates that the source of sediments is in the headwaters (Delaney et al 2018;Chalov et al 2017;Baca 2008).…”
Section: Introductionmentioning
confidence: 99%